If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 44 = h + -33 Reorder the terms: 44 = -33 + h Solving 44 = -33 + h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1h' to each side of the equation. 44 + -1h = -33 + h + -1h Combine like terms: h + -1h = 0 44 + -1h = -33 + 0 44 + -1h = -33 Add '-44' to each side of the equation. 44 + -44 + -1h = -33 + -44 Combine like terms: 44 + -44 = 0 0 + -1h = -33 + -44 -1h = -33 + -44 Combine like terms: -33 + -44 = -77 -1h = -77 Divide each side by '-1'. h = 77 Simplifying h = 77
| 8/x=12/3 | | 8w-15w=35 | | 55=k-29 | | Y/3.5=10 | | 41=y+19 | | y-7=2.66(x-10) | | 4[4-(3-7x)]+2x=5(6x+3)-11 | | -1+2=2+3(2-1) | | 39+b=50 | | 3/8=x/1 | | c-3=13 | | 3(sin)x+1=(sin)x | | 10/1=x/2 | | 12x+9=8x+3+4x | | x+24=28 | | 62+5x=3(-x+3)-11 | | .09x+.11(x+9000)=2590 | | 2f=86 | | 33=-3f | | 2.5d+3.25=1+3.25 | | -7-13=9x+18-18x | | -70=7k | | 0=4/15y-28 | | 1/x=7/3 | | 7-8d=39 | | 1.08y=y+48 | | 3x-55+2x=5y | | Y+4.7=-8.6-5.3 | | -4x+6-5(x-1)=-(3x-3)-5x+5 | | X-0.2=6.4 | | 5x-2(3-4x)=3(x-3)-57 | | (4f^2-3)+11f=0 |